Towards Sustainable Production of Potato under Climate Change Conditions - Rabia, Ahmed H.; Yacout*, Dalia M. M.; Shahin, Sara F.; Mohamed, A.A.A.; Abdelaty, Emad Fawzy (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Nile delta of Egypt is one of the most vulnerable areas subjected to climate change impacts. A large portion of our agricultural cultivation is mainly accumulated in the Nile delta. As a result the agricultural cultivation is facing several challenges due to climate change impacts especially extreme climatic events. This leads to a significant drop in potato production consequently negative socio-economic impacts all over the country. The aim of this paper was to investigate the climate change impacts on one of Egypt’s top strategic crops, potato. It was found that assessing climate change impacts on potato cultivation at local level is required. Increasing losses in crop production and quality have been taking place due to climate change in Egypt. It is very useful to identify proper adaptation practices for mitigating climate change impacts in potato production. Decision makers in developing adaptation strategies for potato production in Egypt should be assisted.